EDUKASI K3 UNTUK KESUKSESAN KERJA: MENINGKATKAN PERFORMA DAN EFESIENSI KERJA - Fadhil, Aqilah Al Afif; Sahrir, Sukmawati Sultan; Bustamin, Syamsumar (Universitas Methodist Indonesia, 2023)
K3 assistance focuses on optimizing work performance through the implementation of effective K3 practices. This involves training college and female students on relevant safety measures, understanding risks, and adhering to safe work procedures. Through intensive assistance, students can acquire the knowledge and skills needed to carry out their duties safely. In addition to improving performance, K3 assistance also improves employee work efficiency. By ensuring a safe and healthy work environment, OSH assistance encourages a sense of comfort and trust in the workplace. This has a positive impact on productivity, motivation, and job satisfaction. This approach also pays attention to aspects of psychological wellbeing, such as managing stress, increasing resilience, and creating a positive work climate. K3 assistance for work success also involves effective communication between management and employees. Through open and transparent dialogue, challenges and problems related to OSH can be identified and overcome together. This assistance also includes monitoring and evaluating the implementation of K3 practices, so that necessary improvements and adjustments can be made.